World Risk Society and Constructing Cosmopolitan Realities: A Bourdieusian Critique of Risk Society - Jong, Abbas (Frontiers in Sociology, 2022)
Current global crises and threats have revealed the growing implications of Ulrich Beck’s theory of risk society. Rather than being a theory of risk, risk society theory is more a social theory of the new social world and modernity. Risk society theory encompasses a new social ontology of the social in the era of uncertainties and crises. Beck also proposes the cosmopolitan outlook and particularly methodological cosmopolitanism as the epistemology and methodology of the world risk society. Yet, a close examination of Beck's social theory reveals a contradiction between the two aspects. On the one hand, in the ontological dimension, we are faced with the primacy of the indeterminate and the empirical, but on the other hand, Beck's epistemological prescriptive eliminate the possibility of reaching them. The current article aims to address this incompatibility. In doing so, first, the main pillars of risk society theory, and then the cosmopolitan outlook and sociology are discussed. By criticizing Beck’s epistemological apparatus as well as juxtaposing the theory of risk society and Pierre Bourdieu’s theory of action and fields, in the final section, the article proposes a solution to complete the ontology of risk society and overcome some of its epistemological problems.